Utilization and prescribing patterns of direct oral anticoagulants - Whitworth MM; Haase KK; Fike DS; Bharadwaj RM; Young RB; MacLaughlin EJ (International Journal of General Medicine, 2017)
Maegan M Whitworth,1 Krystal K Haase,1 David S Fike,1 Ravindra M Bharadwaj,2 Rodney B Young,3 Eric J MacLaughlin1,4 1Department of Pharmacy Practice, Texas Tech University Health Sciences Center (TTUHSC) School of Pharmacy, 2Department of Internal Medicine, 3Department of Family and Community Medicine, 4Departments of Family Medicine and Internal Medicine, TTUHSC School of Medicine, Amarillo, TX, USA Background: Scant literature exists evaluating utilization patterns for direct oral anticoagulants (DOACs). Objectives: The primary objective was to assess DOAC prescribing in patients with venous thromboembolism (VTE) and nonvalvular atrial fibrillation (NVAF) in outpatient clinics. Secondary objectives were to compare utilization between family medicine (FM) and internal medicine (IM) clinics, characterize potentially inappropriate use, and identify factors associated with adverse events (AEs). Methods: This was a retrospective cohort study of adults with NVAF or VTE who received a DOAC at FM or IM clinics between 10/19/2010 and 10/23/2014. Descriptive statistics were utilized for the primary aim. Fisher’s exact test was used to evaluate differences in prescribing using an adapted medication appropriateness index. Logistic regression evaluated factors associated with inappropriate use and AEs. Results: One-hundred twenty patients were evaluated. At least 1 inappropriate criterion was met in 72 patients (60.0%). The most frequent inappropriate criteria were dosage (33.0%), duration of therapy (18.4%), and correct administration (18.0%). Apixaban was dosed inappropriately most frequently. There was no difference in dosing appropriateness between FM and IM clinics. The odds of inappropriate choice were lower with apixaban compared to other DOACs (odds ratio [OR]=0.088; 95% confidence interval [CI] 0.008–0.964; p=0.047). Twenty-seven patients (22.5%) experienced an AE while on a DOAC, and the odds of bleeding doubled with each inappropriate criterion met (OR=1.949; 95% CI 1.190–3.190; p=0.008). Conclusion: Potentially inappropriate prescribing of DOACs is frequent with the most common errors being dosing, administration, and duration of therapy. These results underscore the importance of prescriber education regarding the appropriate use and management of DOACs. Keywords: rivaroxaban, dabigatran, apixaban, atrial fibrillation, venous thromboembolism, medication errors